Challenges and opportunities for designing clinical trials for antibody mediated rejection - Balakrishnan, Suryanarayanan; Alexander, Mariam P.; Schinstock, Carrie (Frontiers in Transplantation, 2024)
Significant progress has been made in kidney transplantation, with one-year graft survival nearing 95% [1]. However, long-term allograft survival remains suboptimal, with a 10-year overall graft survival rate of only 53.6% for deceased donor transplant recipients [2]. Chronic active antibody-mediated rejection (ABMR) is a leading cause of death-censored graft loss [3][4], yet no therapy has demonstrated efficacy in large, randomized trials, despite substantial investment from pharmaceutical companies.Several clinical trials aimed to treat chronic ABMR in the past decade have yielded disappointing results or were prematurely terminated [5][6][7], attributed to factors including incomplete understanding of disease mechanisms, heterogeneous patient populations with comorbidities, slow disease progression, and limited patient numbers. This review aims to discuss opportunities for improving retrospective and prospective studies of ABMR, focusing on addressing heterogeneity, outcome measurement, and strategies to enhance patient enrollment to inform study design, data collection, and reporting.